DEVELOPMENT OF MALAPARI OIL CATALYTIC CRACKING FOR BIO-BASED GASOLINE - Idham K.A. DR, Muhammad
Indonesia's dependence on fuel makes total gasoline imports increase. This resulted in the depletion of the country's foreign exchange reserves and state budget deficit. Therefore, there is need to look for energy from other sources especially that come from within the country. One of the natural resources that can be used as an alternative material that can be converted to fuel is malapari. Malapari can produce as much as 2 tons of fatty oil / hectare / year. In addition, malapari can grow in almost all types of habitat including dry land. Malapari oil conversion to gasoline can be done in several ways such as thermal cracking, catalytic cracking and hydrocracking. The catalytic cracking reaction is more economical and efficient because it requires less heat than thermal cracking and high product conversion compared to hydrocracking. In this research, a catalytic cracking reaction was carried out in a batch reactor with a temperature of 500°C and a catalyst mass of 2.5 grams. To determine the effect of catalyst on the yield and selectivity of liquid products, variations were made between 2 different types of zeolite with catalyst ratios of 2 types successively 1:0, 0:1, 3:1, 2:3 1:1, 1:3 and 1:4. In addition, variations of WHSV were carried out to determine the effect of operating conditions on the yield, selectivity and composition of hydrocarbons in gasoline. Variation of operating conditions was carried out with a ratio of 2 types of catalyst on 1:3, while WHSV variations were 2.5, 1.5, 2 and 3 respectively. Result shows gasoline made from malapari oil has lower gasoline selectivity than gasoline made from palm oil. Results also shows variation of catalyst ratio 3:1 has higher gasoline selectivity and octane number. However, this variation hasn’t fulfill the specifications of Indonesia gasoline because it has high content of aromatic hydrocarbon. Research also shows WHSV 2,5 has optimum liquid product yield at 53,74% and high gasoline selectivity.